Standardisation of Media and containers for Ex-Vitro Establishment of Anthurium Plantlets produced by Leaf culture - Ajith Kumar PV (Department of Horticulture, College of Agriculture, 1993)
Investigations were carried out at the Plant Tissue Culture Laboratory of the College of Agriculture, Vellayani during 1991-1993 to develop suitable methods to plant out Anthurium andreanum plantlets and to standardise media and